(untitled) - Marsh, Lisa (Hoboken, N.J., 2003)
From Mosholu Parkway to the high fashion salons of Paris and Milan, Lisa Marsh takes us on a Mach-1 ride through the world of Calvin Klein. A well-told tale of a boy from the Bronx who revolutionized fashion and made himself rich, yet somehow failed to make himself happy. The essential, and eternal, morality play of business
Keywords: Fashion designers,Fashion designs; History; 20th century; United states,United states